PENGARUH IKLIM ORGANISASI DAN STRES KERJA TERHADAP KEPUASAN KERJA GURU PADA SMP NEGERI 1 BANJARANGKAN KLUNGKUNG - Cokorda Agung Satya Pramantha; I Wayan Widnyana; I Gst Ngr Bagus Gunadi (VALUES, 2022)
This study aims to examine the effect of organizational climate and job stress on teacher job satisfaction. The success of a teacher in providing knowledge cannot be separated from the factor of whether the teacher is satisfied in doing his job, because teacher dissatisfaction at work has an impact on the teaching and learning process that is not optimal. The existence of a good organizational climate will be able to lead to job satisfaction, teachers who are in a good and conducive organizational climate will be able to create teacher initiatives to want to do an activity and work that is an obligation and also do not hesitate to carry out tasks outside of their work. Teacher job satisfaction also has something to do with work stress, stress forces a person to deviate from normal functions due to changes that interfere with or improve physiological and psychological conditions, so they are forced to deviate from normal functions. This research was conducted at SMP Negeri 1 Banjarangkan which is located at Jalan Lettu Ida Bagus Puja. The sample in this study was as many as 61 teachers with the sample being taken using the population or census method. The analytical tool used is multiple linear regression analysis. The results showed that the organizational climate had a positive and significant effect on teacher job satisfaction. And work stress has a negative and significant effect on teacher job satisfaction. Then the organizational climate and work stress together have an effect of 78.7% on teacher job satisfaction.